A facile synthesis of pyrrolo[2, 3‐j]phenanthridines via the cascade reaction of indoleanilines and aldehydes. (26th January 2022) - Huang, Wen‐Jun; Chen, Zhi‐Peng; Liu, Li‐Xia; Zhou, Yong‐Gui; Wu, Bo; Jiang, Guo‐Fang
Abstract: A facile method for the synthesis of pyrrolo[2, 3‐ j ]phenanthridines from indoleanilines and aldehydes in the presence of Brønsted acid catalyst and benzoquinone oxidant has been established. This approach features excellent yields, high efficiency and a wide range of substrate scope. Mechanism studies exhibited that this reaction was a cascade process including acid‐catalyzed condensation of indoleanilines with aldehydes, cyclization and oxidative aromatization. Abstract :